Automation of Educational Institution Documentation - V. V. Sivakov; A. A. Solomnikov; I. Yu. Adamovich; S. P. Stroev (Moscow Polytechnic University, 2021)
The article addresses issues related to the implementation of the competence approach in order to make the teaching process of an educational institution more efficient, analyzes the reasons for diminished efficiency of putting into practice the automated systems used for university management. The authors propose the structure of an automated system, which allows the university to create the required package of teaching documents taking into account the three-level system: administrator, supervisor of educational program, and lecturer. Designing object-oriented model in the area of a special subject requires identification of business-requirements to the system. On the basis of the model of subject area and specified business-requirements, the diagram of applying variants and the schemes of functioning is constructed. The suggested system of the automated execution of teaching documents enables to reduce error rate while carrying out and implementing it due to the integrated system of conceptions and feedback between its elements.